2011
DOI: 10.1017/s0962728600002888
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of farmer recognition and reporting of lameness in adults in 35 lowland sheep flocks in England

Abstract: The aim of this study was to assess the accuracy of farmer recognition and reporting of lameness in their sheep flock when compared with the prevalence of lameness observed by a researcher. Thirty-five sheep farms were visited. Farmers were asked for estimates of the prevalence of lameness in 2008, in the flock and in one group of sheep that was inspected by the researcher the same day. These estimates were then compared with the researcher's estimate of lameness. All farmers were able to recognise lame sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Accurate assessment of lameness prevalence is important for ensuring appropriate prevention measures and prompt treatment ( 14 ). Studies have shown that farmers can have a low awareness or knowledge of lameness, underestimate lameness in their herd or flock, or becoming desensitized to lame animals ( 14 , 37 , 39 , 40 ). Previous research has shown that the emotional aspects of motivation affect behavior ( 13 ) and that habit is often a barrier to changing farmer behavior ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate assessment of lameness prevalence is important for ensuring appropriate prevention measures and prompt treatment ( 14 ). Studies have shown that farmers can have a low awareness or knowledge of lameness, underestimate lameness in their herd or flock, or becoming desensitized to lame animals ( 14 , 37 , 39 , 40 ). Previous research has shown that the emotional aspects of motivation affect behavior ( 13 ) and that habit is often a barrier to changing farmer behavior ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that perceptions and understandings of lameness present particular challenges for its effective management. A lack of awareness of lameness (37), inaccurate perceptions of lameness levels (38), or underestimated levels all make early identification and treatment difficult (24,(39)(40)(41). Moreover, for some farmers, lameness is simply accepted as an inevitable part of farming process (29,32,42).…”
Section: Challenges In Lameness Managementmentioning
confidence: 99%